Relationship of compositions, criteria and indicators of preparation of a future geography teacher to professional activities on the basis of a competence approach - Oleksandra Chubrei (Kazimierz Wielki University, 2019)
The article defines and substantiates the ratio of components, criteria and indicators of future geography teacher's readiness for professional activity on the basis of competence approach. In order to identify the criteria for the formation of the phenomenon under study, the essence of the terms "criterion", "indicator" and "level" are defined. Based on the analysis and own vision, it was determined that the main criteria for the future geography teacher's preparation for professional activity on the basis of a competent approach are knowledge, skills and values of personality. Auto-psychological, self-organizing, reflexive, self-educational, organizational, leadership and technological components were found to be components of preparedness.Based on the generalization of these criteria and relevant indicators, we have established the level of preparedness of future geography teachers: low, sufficient, medium and high.